Peningkatan Literasi Digital Anak Usia Dini melalui Pembelajaran Interaktif Berbasis Teknologi di Kecamatan Alam Barajo, Kota Jambi - Kasmiati, Kasmiati (Universitas Pahlawan Tuanku Tambusai, 2026)
The development of digital technology has influenced nearly all aspects of life, including early childhood education. However, at this level, digital literacy is often perceived merely as using electronic devices without understanding how to learn and interact responsibly in digital spaces. This community service activity aimed to enhance digital literacy among early childhood learners in Alam Barajo District, Jambi City, through technology-based interactive learning. The implementation involved teacher training and direct assistance for children using digital media such as educational videos, interactive applications, and age-appropriate online games. Evaluation was conducted through observation and interviews with teachers and parents to assess improvements in children’s digital understanding and behavior. The results showed greater enthusiasm for learning, improved digital skills (recognizing icons, colors, letters, and sounds), and increased awareness among teachers and parents about the importance of guided digital use. This initiative serves as a model for strengthening early childhood digital literacy in Jambi City.